Control of a Back-To-Back Modular Multilevel Matrix Converter for Low Frequency Ac Transmission - Espina-Gonzalez, E; Diaz-Diaz, M; Pizarro-Jimenez, P; Rojas-Aceituno, A (Institute of Electrical and Electronics Engineers Inc., 2023)
The Modular Multilevel Matrix Converter (M3C) has been indicated as a suitable option for Low-Frequency Alter-nating Current (LFAC) transmission due to some characteristics such as simple power and voltage extensibility, controllability and high efficiency. The control of the M3C in LFAC is simplified because the floating capacitor voltage oscillations are relatively small. However, when connecting to AC ports of different frequencies, AC transformers at fractional or nominal frequencies may be required. This can lead to an increase in the built-in ratio of such systems. To address this issue, this paper proposes a simple control strategy for a Back-to-Back M3C equipped with a medium-frequency port. Simulation results for validating the topology and control system of a high-power LFAC application are presented for a 396 MW case study. © 2023 IEEE.